Bearing characteristics of variable diameter micropile based on the improvement of group pile foundation - Guangming REN; Haitao LI; Biyang WANG; Rongquan FAN; Bin DONG; Yi LUO (Shuiwen dizhi gongcheng dizhi, 2024)
To improve the load-bearing of transmission tower micropile foundation and reduce the material cost, a modified variable diameter micropile foundation type based on group micropile is proposed in this study. The bearing characteristics and deformation mechanism of variable diameter miniature pile were revealed by simulation with three kinds of variable diameter miniature micropiles and comparison with the bearing effect of micropile group pile, using the prototype test and numerical inversion model of micropile group pile with equal section in the highland mountainous area. The results show that the compressive and pullout bearing capacities of micropile group foundation (2×2 single pile) are greater and less than the total of corresponding single pile bearing capacity, respectively, due to the effect of bearing platform and group pile effect. The ultimate pullout and compressive bearing capacities of double diameter-extended micropile (the diameter of the dilated part = 2 × the diameter of the equal) is approximately 3.8 times and 2.7 times of the equal section micropile. The soil deformation is concentrated in the dilated part with large deformation value, which presents the characteristics of multi-fulcrum friction-end bearing pile. The addition of cap can improve the downward pressure and horizontal bearing capacity of double-expanded micropile effectively, which increase 2.1 times and 2.2 times compared to that in the situation of no cap, respectively. This study indicates that improving the performance of single micropile to the level of equal section group micropiles by extending part of the pile diameter is feasible and has engineering significance for the transmission and substation construction.